Identification of the attitude dynamics for a variable-pitch quadrotor UAV - Riccardi, F.; Panizza, P.; Lovera, M. (My University, 2014)
System identification is an established approach for the derivation of control-oriented dynamic models in the rotorcraft field (see for example the survey paper [9], the recent books [19] [10] and the references therein). While the application to full scale rotorcraft is by now fairly mature, less experience has been gathered on small-scale vehicles, such as, e.g., quadrotor UAVs. In this paper the problem of characterizing the attitude dynamics of a variable-pitch quadrotor from data is considered and the results obtained in an experimental identification campaign are presented and discussed. More precisely, in this study both on-line and on-line methods have been considered and the performance of black-box versus grey-box models has been compared.